Ultrashort Echo Time Quantitative Susceptibility Mapping (UTE-QSM) for Detection of Hemosiderin Deposition in Hemophilic Arthropathy: a Feasibility Study - Jang, Hyungseok (Magn Reson Med, 2020)
PURPOSE: The purpose of this study was to investigate the feasibility of ultrashort echo time quantitative susceptibility mapping (UTE-QSM) for assessment of hemosiderin deposition in the joints of hemophilic patients. METHODS: The UTE-QSM technique was based on three sets of dual-echo 3D UTE Cones data acquired with TEs of 0.032/2.8, 0.2/3.6, and 0.4/4.4 ms. The images were processed with Iterative Decomposition of water and fat with Echo Asymmetry and Least-squares estimation (IDEAL) to estimate the B(0) field map in the presence of fat. Then, the projection onto dipole field algorithm was applied to acquire a local field map generated by tissues, followed by application of the morphology-enabled dipole inversion algorithm to estimate a final susceptibility map. Three healthy volunteers and three hemophilic patients were recruited to evaluate the UTE-QSM technique’s ability to assess hemosiderin in the knee or ankle joint at 3T. One patient subsequently underwent total knee arthroplasty after the MR scan. The synovial tissues harvested from the knee joint during surgery were processed for histological analysis to confirm iron deposition. RESULTS: UTE-QSM successfully yielded tissue susceptibility maps of joints in both volunteers and patients. Multiple regions with high susceptibility over 1 ppm were detected in the affected joints of hemophilic patients, while no salient regions with elevated susceptibility were detected in asymptomatic healthy volunteers. Histology confirmed the presence of iron in regions where high susceptibility was detected by UTE-QSM. CONCLUSION: The UTE-QSM technique can detect hemosiderin deposition in the joint, and provides a potential sensitive biomarker for the diagnosis and prognosis of hemophilic arthropathy (HA).